A non-intrusive seismic retrofitting technique for masonry infills based on bed-joint sliding. (15th June 2023) - Vailati, Marco; Gregori, Amedeo; Mercuri, Micaela; Monti, Giorgio
Abstract: In recent years, several seismic retrofitting projects of existing buildings have been involving additional measures to improve their energy efficiency, thanks to new regulations aiming at optimizing the buildings overall performance. Significant improvement is usually obtained through radical measures aiming at strengthening the infill panels, typically vulnerable to both out-of-plane overturning and in-plane cracking, and at enhancing their thermal insulation. Measures not disrupting the internal activities are generally favored. Back in 2012, two of the authors proposed a seismic-resistant double-layered infill panel for new buildings endowed with innovative flexible dissipative joints, placed along the horizontal brick interfaces, made from recycled plastic. In this work, those joints are upgraded to be used for retrofitting infill panels made of double-layered bricks and intermediate hollow space, as typical in most existing buildings. Within an existing infill panel, such joints create a system of parallel sliding surfaces along the horizontal bed-joints, after cutting off the mortar layer, thus channeling the in-plane deformation in the joints. On passing, it is noticed that the out-of-plane resistance is ensured by cantilevering elements protruding outwards from the joints surface, which prevent the panel from developing out-of-plane mechanisms. Such system has been preliminarily tested on a real-scale double-layer infill equipped with two joint lines under horizontal force. The experimental results have been compared with analytical models available in the literature for assessing stiffness and strength of the possible failure mechanisms, and a modified equation has been proposed for the mechanism involving bed-joint sliding induced by plastic joints. Highlights: Innovative seismic retrofitting technique of masonry infills based on bed-joint sliding using recycled plastic devices. Suitable for buildings with double-layer infilled frames in seismic zones with brittle behavior and/or low thermal performances. Manufacturing of the structural components (i.e. the joints) with 3d printing technique. It can be used without disrupting the daily internal activities. Recycled plastic reduces the consumption of water, aggregates and binder, while renewing the life cycles of plastic waste.